Indeks Massa Tubuh (IMT) Sebagai Prediktor Hipertensi: Perbandingan Standar WHO dan Asia-Pasifik : Indeks Massa Tubuh sebagai Prediktor Hipertensi: Perbandingan Standar World Health Organization dan Asia-Pasifik - Mulyasari, Indri; Afiatna, Puji; Maryanto, Sugeng; Aryani, Aisyah Nur (Universitas Airlangga, 2023)
Background: BMI is associated with increase in blood pressure. Asia-Pacific BMI recommendation has lower cut-off for overweight and obesity categories than WHO standard. Objectives: To analyze sensitivity of BMI based on WHO and Asia-Pacific recommendation for predicting hypertension. Methods: This study was diagnostic research. Population of this study was women employees in a Garment company in Semarang Regency aged 19-54 years. Total sample was 180 taken using simple random sampling technique. Sensitivity of BMI was analyzed using ROC. Results: Prevalence of overnutrition based on WHO criteria is 30.6% and 87.8% based on Asia-Pacific criteria. Sample with hypertension are 85% and not hypertension 15%. BMI is very good on predicting hypertension with AUC 95.5%. WHO and Asia-Pacific BMI recommendation are associated with blood pressure (p<0.001, r=0.278, 0.450 respectively). Asia-Pacific BMI recommendation has better sensitivity than WHO recommendation (Se=95.4%, Se=35.9%). Conclusions: Asia-Pacific BMI recommendation is more suitable for predicting hypertension in adult women in Indonesia.